Individual optimization of the repulsion biomechanism When jumping up - Bilenko, A.G.; Losin, B.E.; Ivanova, G.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to find the optimal repulsion technique depending on the individual characteristics of the athlete. Methods and structure of the study. The research procedure included performing an upward jump on a dynamometer platform and analyzing the vertical component of the support reaction. Results and conclusions. As a result, according to the information received about the height and efficiency coefficient of each of the jumps performed using various techniques, the most rational individual movement stereotype of repulsion from the support is determined when the subject performs a series of jumps. The efficiency coefficient quantitatively assesses the quality of the organization of the jumping movement with the possibility of operational control of various variants of the repulsion biomechanism. In the aspect of improving biomechanical analysis: the proposed research methodology implements one of the possible approaches to studying the operation of open biomechanical systems, in contrast to the previously used point mass models. The results of the study will help to gain knowledge about the biomechanics of repulsion and form an individual technique based on operational feedback.